Relationship Between Maternal Vitamin D Deficiency and Newborn Anthropometry: Maternal Vitamin D Deficiency and Newborn Anthropometry - Ahmed, Ayesha; Memon, Shazia; Shaikh, Farzana; Parveen, Fahmida (Pakistan Journal of Health Sciences, 2023)
Intrauterine development restriction and low birth weight in the newborn are two negative pregnancy outcomes that can result from maternal hypovitaminosis D. Objective: To determine the association between maternal vitamin D level and neonatal anthropometry (birth-weight, birth length and head circumference). Methods: This cross-sectional research was conducted in Post-Natal Ward of Liaquat University of Medical and Health Sciences, Hyderabad/Jamshoro, after getting official permission from July 2021 to Dec 2021. Healthy Mothers with alive Newborn aged < 24 hours were enrolled via Non-probability, convenience sampling. After taking due approval and written informed consent from mothers. Data were collected into a structured questionnaire, containing enquiries pertaining to basic biodata, sociodemographic details, Vitamin D levels, and anthropometric measurements of baby. Results: The mean age of the mothers was 26.82 (SD ± 7.4) years, predominantly hailing from urban areas (78.5%), with a mean BMI of 23.702 kg/m2 (SD ± 4.32). A low birth weight was reported in 53% while very low birth weight was reported in 4% of the cases. Majority of neonates were found to be of small for gestational age irrespective of their gestational age of delivery. Conclusions: In compared to babies whose mothers had adequate levels of vitamin D, the study reported that babies of moms with lower levels of vitamin D have smaller birth weights and are smaller for gestational age